2020
DOI: 10.1186/s12964-020-00662-2
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsically disordered region of GCE protein adopts a more fixed structure by interacting with the LBD of the nuclear receptor FTZ-F1

Abstract: The Drosophila melanogaster Germ cell-expressed protein (GCE) is a paralog of the juvenile hormone (JH) receptor - Methoprene tolerant protein (MET). Both proteins mediate JH function, preventing precocious differentiation during D. melanogaster development. Despite that GCE and MET are often referred to as equivalent JH receptors, their functions are not fully redundant and show tissue specificity. Both proteins belong to the family of bHLH-PAS transcription factors. The similarity of their primary structure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 87 publications
4
27
0
Order By: Relevance
“…With regard to the regulation of Met subcellular localization, the JH-dependent nuclear localization signal in the PAS-B+ domain may outweigh phosphorylation modification ( Greb-Markiewicz et al, 2011 ). Previous studies have shown that the JH-dependent nuclear import of the PAS-B+ domain of Met is responsible for binding of the nuclear receptor Ftz-F1 ( Bernardo and Dubrovsky, 2012 ; Kolonko et al, 2020 ). Conceivably, loss of phosphorylation modification in the PAS-B+ domain of Met could have no effect on JH intracellular signaling activity in Drosophila , differing from the report that T393 phosphorylation in the PAS-B domain is critical for Kr-h1 transcription in H. armigera ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the regulation of Met subcellular localization, the JH-dependent nuclear localization signal in the PAS-B+ domain may outweigh phosphorylation modification ( Greb-Markiewicz et al, 2011 ). Previous studies have shown that the JH-dependent nuclear import of the PAS-B+ domain of Met is responsible for binding of the nuclear receptor Ftz-F1 ( Bernardo and Dubrovsky, 2012 ; Kolonko et al, 2020 ). Conceivably, loss of phosphorylation modification in the PAS-B+ domain of Met could have no effect on JH intracellular signaling activity in Drosophila , differing from the report that T393 phosphorylation in the PAS-B domain is critical for Kr-h1 transcription in H. armigera ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal NLSs reside in proline/serine/threonine-rich regions that are intrinsically disordered in both D. melanogaster GCE ( 69 , 72 ) and T. castaneum methoprene-tolerant proteins ( Fig. 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed as described previously ( Kolonko et al, 2020 ). In short, African green monkey kidney fibroblast COS-7 cells (ATCC CRL-1651) were grown in Ø6 cm plates at 37°C 24 h prior to transfection (Xfect Transfection Reagent Takara Bio) with 9 μg of the appropriate vector encoding the selected protein, or with 6 μg of each from two selected vectors in the case of co-transfection.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to bHLH and PAS domains presenting high sequence homology (78% for bHLH, 68% for PAS-1, and 86% for PAS-2) ( Moore et al, 2000 ), the C-termini of Met and Gce (MetC and GceC, respectively) are highly differentiated ( Supplementary Figure S1 , based on the SIM server ( Huang and Miller, 1991 )) ( Moore et al, 2000 ; Kolonko et al, 2016 ; Kolonko et al, 2020 ). Variable C-terminal fragments of bHLH-PAS proteins were shown to comprise transactivation domains (TADs, as described by Moffett and Pelletier (2000 )) and are considered important elements modulating protein activity ( Kewley et al, 2004 ; Furness et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%